Dynamics in the Strawberry Rhizosphere Microbiome in Response to Biochar and Botrytis cinerea Leaf Infection - De Tender, Caroline; Haegeman, Annelies; Vandecasteele, Bart; Clement, Lieven; Cremelie, Pieter; Dawyndt, Peter; Maes, Martine; Debode, Jane (Frontiers in Microbiology, 2016)
Adding biochar, the solid coproduct of biofuel production, to peat can enhance strawberry growth and disease resistance against the airborne fungal pathogen Botrytis cinerea. Additionally, biochar can induce shifts in the strawberry rhizosphere microbiome. However, the moment that this biochar-mediated shift occurs in the rhizosphere is not known. Further, the effect of an above-ground infection on the strawberry rhizobiome is unknown. In the present study we established two experiments in which strawberry transplants (cv. Elsanta) were planted either in peat or in peat amended with 3% biochar. First, we established a time course experiment to measure the effect of biochar on the rhizosphere bacterial and fungal communities over time. In a second experiment, we inoculated the strawberry leaves with B. cinerea, and studied the impact of the infection on the bacterial rhizobiome. The fungal rhizosphere community was stabilized after one week, except for the upcoming Auriculariales, whereas the bacterial community shifted till six weeks. An effect of the addition of biochar to the peat on the rhizosphere microbiome was solely measured for the bacterial community from week six of plant growth onwards. When scoring the plant development, biochar addition was associated with enhanced root formation, fruit production and postharvest resistance of the fruits against B. cinerea. We hypothesize that the rhizosphere bacteriome, but also biochar-mediated changes in chemical substrate composition could be involved in these events. Infection of the strawberry leaves with B. cinerea induced shifts in the bacterial rhizobiome, with an increased bacterial richness. This disease-induced effect was not observed in the rhizospheres of the B. cinerea-infected plants grown in the biochar-amended peat. The results show that an above-ground infection has its effect on the strawberry rhizobiome, changing the bacterial interactions in the root–substrate interface. This infection effect on the bacterial rhizobiome seems to be comparable to, but less pronounced than the effect of biochar-addition to the peat. The biological meaning of these observations needs further research, but this study indicates that biochar and an above ground pathogen attack help the plant to recruit rhizosphere microbes that may aid them in their plant growth and health.